Pricing longevity swaps : an empirical investigation using the risk-neutral simulation method - Santos, Sofia Alexandra Vieira dos (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management